Optical transmission spectra study in visible and near-infrared spectral range for identification of rough transparent plastics in aquatic environments. (June 2020) - Kanyathare, Boniphace; Asamoah, Benjamin O.; Ishaq, Umair; Amoani, James; Räty, Jukka; Peiponen, Kai-Erik
Abstract: Erosion of microplastics due to residence time in aquatic environments causes roughening of the microplastic. Unfortunately, currently used measurement methods do not provide information on the surface roughness of the microplastic embedded in water. In this study we propose a novel method by using transmittance to get information on the magnitude of the surface roughness of microplastics and to rank microplastics by thickness. For such a purpose, we studied optical properties such as dispersion, absorption of both plastics and water in the partial spectral range of visible light (Vis), transmission and scattering of light by plastic sheets, as well as, the calculated sample thickness in the Vis region. These were explored for the detection of both smooth and roughened plastic sheets immersed in water. Moreover, by using the transmission spectrum and refractive index of both plastic and water it is possible to estimate the average surface roughness of plastic samples. Our results suggest that the optical properties in the Vis region offer an interesting way for the detection of both rough and smooth plastic sheets and for ranking the type of plastics in an aquatic environment. Graphical abstract: Image 1 Highlights: Estimate surface roughness of microplastics by transmittance & refractive index. Differentiating rough from smooth microplastics by transmittance trends. Ranking microplastics by transmittance. Ranking microplastics by thickness.